2000
DOI: 10.1021/jo000967l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrimidine 2‘-Deoxy Ribonucleosides Branched at the 2‘-Position via Radical Atom-Transfer Cyclization Reaction with a Vinylsilyl Group as a Radical-Acceptor Tether1

Abstract: Recently, we developed a regio- and stereoselective method for introducing a vinyl group at the position beta to a hydroxyl group in halohydrins or alpha-phenylselenoalkanols via a radical atom-transfer cyclization reaction with a vinylsilyl group as a temporary connecting radical-acceptor tether. The synthesis of 2'-deoxy-2'-C-vinyl- and 2'-deoxy-2'-C-hydroxymethyluridines (7 and 8, respectively) and the corresponding 2'-deoxycytidine congeners (10 and 11, respectively), which were designed as potential antit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…Besides their potential biological activity as antiviral agents, the C1 0 -branched nucleosides show further great interest, linked to the availability of model nucleosides which may allow the study of the formation and evolution of radical species generated during DNA/RNA damage. 4 N,O-psiconucleosides 4 constitute a particular class of modified psiconucleosides where an isoxazolidine system mimics the ribose ring of natural nucleosides and a hydroxymethyl group is linked at the anomeric carbon atom. 5 These derivatives show synthetic interest for their potential antiviral or anticancer activity which have been also discovered in other N,O-nucleosides.…”
Section: Introductionmentioning
confidence: 99%
“…Besides their potential biological activity as antiviral agents, the C1 0 -branched nucleosides show further great interest, linked to the availability of model nucleosides which may allow the study of the formation and evolution of radical species generated during DNA/RNA damage. 4 N,O-psiconucleosides 4 constitute a particular class of modified psiconucleosides where an isoxazolidine system mimics the ribose ring of natural nucleosides and a hydroxymethyl group is linked at the anomeric carbon atom. 5 These derivatives show synthetic interest for their potential antiviral or anticancer activity which have been also discovered in other N,O-nucleosides.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of procedures for preparing synthetic branched-chain sugar nucleosides have been described. However, the number of 2Ј-deoxy-2Ј-α-C-branched ribonucleosides reported are limited, [10][11][12][13][14][15] and their biological activities have not yet been investigated in a systematic manner, perhaps because of a lack of the availability of efficient synthetic methods leading to 2Ј-deoxy-2Ј-α-C-branched ribonucleosides.…”
Section: Introductionmentioning
confidence: 99%
“…Only few publications report the synthesis of 2Ј-deoxy-2Ј-α-C-hydroxymethylpyrimidine nucleosides. [10][11][12][13][14][15] As far as we know, the synthesis of 2Ј-deoxy-2Ј-α-C-(hydroxymethyl)purine nucleosides has not been reported yet. Two schemes are used to synthesize such pyrimidine nucleosides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9) Considerable attention has been focused on branched chain sugar nucleosides because of their biological importance. During the course of synthetic studies aiming to develop antitumor agents, our group has found that branched-chain sugar nucleosides [10][11][12][13][14][15][16] are promising antitumor drug candidates 17) such as 1-(2-deoxy-2-methylene-b-Derythro-pentofuranosyl)cytosine [18][19][20][21] (DMDC, Fig. 1, 1) and 1-(2-C-cyano-2-deoxy-b -D-arabino-pentofuranosyl)cytosine [22][23][24][25][26][27] (CNDAC, 2).…”
Section: Introductionmentioning
confidence: 99%